Unveiling the Concept of Taklīf in the Qur’an: A Tahlīlī Study in the Context of Generation Beta - Robiatul Adawiyah Sitorus; Ahmad Zuhri; Mardian Idris Harahap; Insan Akbar (AJIS: Academic Journal of Islamic Studies, 2024)
The principle of taklīf (religious obligation) within the limits of human capacity represents one of God’s blessings upon His creation. Allāh (SWT) has removed hardship in its implementation, ensuring that all individuals can fulfil His commands and avoid His prohibitions. The Qur’an explicitly emphasises that Allāh does not impose a burden beyond the ability of His creatures. The issue addressed in this study concerns the meaning of taklīf in the Qur’an. This inquiry corrects the common misconception among laypeople that paradise can only be attained by those who possess extensive religious knowledge and perform intensive acts of worship—such as highly concentrated prayers, lengthy recitations, abundant deeds, or eloquent Qur’anic recitation. In reality, attaining paradise is not as difficult as often imagined. This research aims to explore and clarify the meaning of taklīf in the Qur’an. The study employs a descriptive-analytical method, which involves presenting all relevant data concerning the subject matter and analysing it by examining the various aspects embedded in the interpreted verses. This research adopts a qualitative, library-based approach. The novelty of this study lies in uncovering the semantic dimensions of taklīf in the Qur’an through key terms such as kataba, faraḍa, lāzim, amara, and wajaba. The findings suggest that taklīf should not be understood merely as a burden, but rather as an obligation intended to facilitate human practice of religion. When individuals immerse themselves excessively in spiritual practices without considering divine ease, they may fail to perform religious duties properly. Islam provides rukhṣah (dispensations) to maintain balance, and neglecting them by insisting on ʿazīmah (the original strict ruling) when concessions are permitted may impose unnecessary hardship. This research concludes that the meaning of taklīf encompasses five key semantic expressions—kataba, faraḍa, lāzim, amara, and wajaba—which collectively convey the sense of obligation and responsibility that does not impose undue difficulty.l